You are on page 1of 7

Chapter 1, Part 3: The Chain Rule

1.
A = hg 0 (t + )
B = sf 0 (a + )
C = sf 0 (a + ) = hg 0 (t + )f 0 (g(t) + t)
D = g 0 (t)f 0 (g(t)).
2. (a) [f (G(t))]0 = f 0 (G(t))G0 (t)
(b)

[f (G(t))]0 =

(2x1 , 2x2 , 1) |x=G(t)

G01 (t)

G02 (t)
G03 (t)

= 2G1 (t)G01 (t)+2G2 (t)G02 (t)G03 (t)

(c) As G(t) A t we have f (G(t)) = k t so [f (G(t))]0 = 0,


giving 0 = f (G(t)) G0 (t), Thus f at G(t) is orthogonal to the curve
given by G(t) at G(t).

3. (a) f (x, y) =

2y

(b) Since f (r(t)) = 0 t we have [f (r(t))]0 = 0 so f (r(t)) r0 (t) = 0, i.e.

x0
ex

=0

0
2y
y

giving
dx x
dy
e 2y
= 0.
dt
dt
But, as
dy
=
dx

dy
dt
dx
dt

we have
dy
ex
= .
dx
2y
4. (a) [f G]0 (t) = f 0 (G(t))G0 (t).

(b) Let G(t) =

x(t)

y(t)
t

then

d
f (x(t), y(t), t) = [f G]0 (t),
dt
so

df (x(t), y(t), t)
=
dt

f (x, y, t)

(c) Since f (x(t), y(t), t) is constant,


0 = x0

x(t)

y (t)
1

= x0

d
f (x(t), y(t), t)
dt

f
f
f
+ y0
+
.
x
y
t

= 0, giving

f
f
f
f
f
f
+ y0
+
= et
+ 2t
+
.
x
y
t
x
y
t

But x = et and y = t2 so
0 = x

f
f
f
+2 y
+
.
x
y
t
2

Another possible answer is


0 = x

f
f
f
2 ln x
+
.
x
y
t

5. (a)
2

f =

2x sin (x 3y)

3 sin (x 3y)

2x

sin (x2

3y)

(b) f (r(t)) r0 (t) = 0 so

2x
x


sin (x2 3y) = 0,


y0
3

i.e. (3y 0 2xx0 ) sin (x2 3y) = 0 so either x2 = 3y or

y0
x0

2x
.
3

(c) Thus
dy
2x
=
.
dx
3
6. (a)
p
(Fi G)
G(x) X
Fi
Gk
= Fi |G(x)
=




xj
xj
k=1 yk G(x) xj x

(b)



F
i


y1

,...,
G(x)


Fi

yp

G1

xj
x

..

G(x)

Gp

xj

(c)

(F1 G)
x1

(F G)0 (x) =

..

(F G)
m
x1

(F1 G)
xn

..

(Fm G)
xn

(d)


1
F

x1 G

..

Fm

x
1


F1

x


1
G

n G x1 x

..
..

.
.



Gp
Fm


xn G
x1 x


G1

x
n

..
.

Gp

xn x

= F0 (G(x))G0 (x).
7.

cos r sin

F0 (r, ) =

sin

r cos

0 (x, y) = (2x 6y, 2y 6x)

( F)0 (r, ) = 0 (F(r, ))F0 (r, )

= (2r cos 6r sin , 2r sin 6r cos )


=

cos r sin

sin

r cos

2r cos2 6r cos sin + 2r sin2 6r cos sin ,

2r2 cos sin + 6r2 sin2 + 2r2 cos sin 6r2 cos2
etc.
8. (a) [F G]0 (a)h = F0 (G(a))G(a)h, so
d(F G)[a; h] = [F G]0 (a)h = F0 (G(a))G0 (a)h
4

= F0 (G(a))dG[a; h]
h

= dF G(a); dG[a; h] .
(b) Note that
dF[r(t); r0 (t)] = F0 (r(t))r0 (t) = [F r]0 (t).
Let h be tangent to the curve given by r(t), at the point r(t). Then h =
kr0 (t) so dF[r(t); h] = k[F(r(t))]0 . Thus dF[r(t); h] is a scalar multiple
of [F(r(t))]0 , and so is tangent to the curve given by F r at the point
F(r(t)). So the mapping h 7 dF[r(t); h] takes vectors tangent to the
curve r(t) at r(t) to vectors tangent to the curve F r at F r(t).
9. Area(P) = | det [h : k]| (where [h : k] is the matrix you get by gluing h and k
together).

h
i
Area(Q) = det dF[a; h] : dF[a; k]

= det F0 (a)h : F0 (a)k



= det (F0 (a)[h : k])


= | det F0 (a)| | det [h : k]|
= | det F0 (a)| Area(P).
The analogous result for IR 3 follows similarly; just use three vectors, say h, k,
and u, etc.
10. (a) [F G]0 (x) = F0 (G(x))G0 (x).
5

(b) The identity matrix I = (x)0 = F0 (G(x))G0 (x), so F0 (y)G0 (x) = I giving


det F0 (y) det G0 (x) = 1


and thus
F G
= 1.
y x
(c)

[F G]0 (x) =

F1
y1

F1
y2

F1
y3

F2
y1

F2
y2

F2
y3

x2
2x1
1

x1

2x2

1
x2 F
y1

F1
y3

2
2
x1 F
2x2 F
+
y1
y2

F2
y3

1
2x1 F
y2

(d)
[F G]0 (x) = F0 (G(x))G0 (x)

G2 (x) G1 (x)
2

2G3 (x)

G1
x1

..

G3
x1

but F G(x) =

G1 G2
2G1 +

G23

x1

x3

so

[F G]0 (x) =

1 0 0

0 0 1

G1
x4

..
.

G3
x4

and thus, by looking at the (1, 1)th entry of [F G]0 (x) we see that

G1
x1

(G2 (x), G1 (x),

2
0)
G
x1

G3
x1

1
2
so G2 G
+ G1 G
= 1.
x1
x1

The other identity has a typo in it. Sorry.

=1